The Effect of Brucellosis on Lipid Profile and Oxidant-Antioxidants Status - Amal H. Ali (College of Pharmacy University of Baghdad, 2017)
The activation of inflammatory cells, the release of their mediators, and the excessive production of free radicals may affect circulating lipids, but no evidence supports a role for peroxidation in the pathogenesis of Brucellosis disease. The aim of this work is to study the effect of Brucellosis on lipid profile concentration and oxidant-antioxidant status. We studied 20 Brucellosis patients (18 Females and 2 males) and 15 healthy controls (age average from 16 to 60 years old). Significant differences were noted between the serum lipids of Brucellosis patients and control group. Mean total cholesterol and low density lipoprotein cholesterol (LDL-cholesterol) concentrations were higher in patients than in control group (mean Â± SE 197.05 Â± 44.7, 165 Â± 37.6). (Pâ‰¤0.004, Pâ‰¤1.59Ã-l0-11) respectively. Whereas, high density lipoprotein cholesterol (HDL-cholesterol) and triglyceride show significant lower  concentration  in  patients  than  control  groups  (mean  Â±  SE  15.12  Â±  3.4  ,  81.22  Â± 18.45)  . (Pâ‰¤ 9Ã-10-6, Pâ‰¤ 9.3Ã-10-7) respectively. Table l , Figure 1.While circulating concentration of glutathione (GSH), soluble antioxidants were higher in Brucellosis patients than in control groups (mean Â± SE 2.49 Â± 0.4). Additionally, increased oxidative stress was observed in the serum of patients with Brucellosis as evidenced by higher malondialdehyde (MDA) concentrations than in control groups (mean Â± SE 270 Â± 9) (Figure 2, Table 1). In conclusion. Disturbances in the lipid profile, and oxidant-antioxidant status occur in Brucellosis patients which may increase incidence of metabolic and cardiovascular events. Key words: Brucellosis disease, Lipid profile, oxidant-antioxidant status.